Exudate and Blood Vessel Feature Extraction in Diabetic Retinopathy Patients using Morphology Operation - Siswo Wardoyo; Anggoro Suryo Pramudyo; Erika Diana Rizanti; Imamul Muttakin (Universitas Ahmad Dahlan, 2016)
Diabetic Retinopathy is one of the retina complications caused by diabetic disease with observable symptoms such as emergence of exudate and new blood vessels. The tool used to screen it is a fundus camera. However, analyzing the fundus image should be done by doctor who is an expert and will require a lot of time. Therefore, automatic feature detection can assist doctor in processing the retinal image in analyzing diabetic retinopathy disease. The proposed method has been tested on the morphological operations of the fundus image from Cicendo Eye Hospital, Bandung. The calculation results on feature extraction exudate area has a range of 0 pixels for normal retinal image, 17-21213 pixel for retinal image NPDR, and 125-12299 retinal image pixel for PDR. The calculation results on the extraction area of blood vessels has a range of 13319-46681 pixel to the normal retina, the retinal image 7435-49938 pixel for NPDR, and 13.81-53.802 retinal image pixel for PDR.